2011
DOI: 10.1177/1943862111415117
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Music on the Production of Neurotransmitters, Hormones, Cytokines, and Peptides: A Review

Abstract: Research on the effects of music exposure on the release of biochemical messengers is an expanding field. The importance of understanding the influence of music on messenger production is a means of explaining behavioral reactions through physiological mechanisms. Signaling molecules that prove integral for important regulatory functions include neurotransmitters, hormones, cytokines, and peptides. Thus music elicits responses promoting positive emotions, alleviation of stress, and immune function. Study of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 35 publications
2
17
0
3
Order By: Relevance
“…Given the role that neuro-transmitters, hormones and the limbic system play in pain according to the NM theory, it is highly relevant that music has been shown to affect the release of endorphins ( 29 37 ), dopamine ( 38 , 39 ) and serotonin ( 40 , 41 ), and decrease cortisol levels ( 39 , 42 47 ). A recent review ( 45 ) of 400 published scientific articles investigating music as medicine found strong evidence that music has effects on brain chemistry, has mental and physical health benefits on management of mood and stress reduction, and that it is the rhythmic stimulation of music, rather than the melody, that has the greatest antipain effect in the brain.…”
Section: Music and Painmentioning
confidence: 99%
“…Given the role that neuro-transmitters, hormones and the limbic system play in pain according to the NM theory, it is highly relevant that music has been shown to affect the release of endorphins ( 29 37 ), dopamine ( 38 , 39 ) and serotonin ( 40 , 41 ), and decrease cortisol levels ( 39 , 42 47 ). A recent review ( 45 ) of 400 published scientific articles investigating music as medicine found strong evidence that music has effects on brain chemistry, has mental and physical health benefits on management of mood and stress reduction, and that it is the rhythmic stimulation of music, rather than the melody, that has the greatest antipain effect in the brain.…”
Section: Music and Painmentioning
confidence: 99%
“…Considering the complexity of auditory processing, it appears plausible that music promotes a variable activation of distinct brain areas, producing different physiological responses. [1][2][3][4][5][6][7][8][9][10][11][12][13] Anaesthetic agents exert both direct and indirect effects on cardiovascular function, resulting in a dose-dependent systemic depression that affects autonomic nervous system parameters, such as heart rate (HR) and arterial blood pressure (ABP). These changes may act as indicators of the depth of anaesthesia in the patient.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the use of motivational auditory stimulus during aerobic exercise was an effective strategy for mood change evaluated by the Brunel Mood Scale, since it increased the positive factor (vigor) and reduced the negative factors (tension, depression, anger, fatigue and mental confusion), thus corroborating our findings. In a review study, Gangrade 16 confirmed the widespread use of music to improve the general well-being of patients.…”
Section: Discussionmentioning
confidence: 91%